The Smart Education & Smart Culture: Digital Innovation as the Key to the Future - Ayu Fitriana; Tri Kamala Lestary (IAHN-TP Palangka Raya, 2026)
Digital transformation has become a key driver of change, particularly in the fields of culture and education in the era of globalization. The concepts of Smart Education and Smart Culture have emerged as strategies to integrate technology in efforts to improve the quality of learning while preserving cultural values. This study employs a literature review method by examining various scientific sources, such as journal articles, books, and research documents relevant to digital education and cultural change. The results of the study indicate that the use of digital technologies—such as online learning platforms, artificial intelligence, and the digitization of culture—can improve access to education, make the learning process more effective, and help preserve and develop local culture. Furthermore, the synergy between Smart Education and Smart Culture helps foster a society that is more innovative, creative, and capable of competing at the international level. Therefore, digital innovation plays a vital role in shaping a better and more sustainable education and cultural landscape.